What IT experts want - A study on how different rewards affect employee engagement - Pajor, Beáta; Szeberényi, András (Marketing & Menedzsment, 2025)
THE AIM OF THE PAPER This study aims to explore the factors that influence employee engagement, with a particular focus on the impact of different types of incentives. The primary goal is to identify which rewards (intrinsic or extrinsic) have a more significant effect on engagement in the Hungarian IT sector. METHODOLOGY A mixed-methods approach was employed, beginning with a comprehensive literature review to examine existing research on factors influencing engagement. The literature revealed contradictions regarding the relative importance of intrinsic versus extrinsic rewards. Based on these insights, the research questions were formulated for the primary research. The study involved a quantitative survey of 226 IT professionals. Descriptive statistics and multiple regression analyses were used to explore the survey results. MOST IMPORTANT RESULTS The study found that extrinsic incentives, especially salary, were the most important factors influencing employee engagement among IT professionals in Hungary's capital. This finding contrasts with some literature that emphasizes intrinsic rewards. However, certain intrinsic incentives also proved to be important, with some consciously valued by employees and others playing an unconscious yet significant role. A statistically significant relationship between rewards and engagement components was confirmed. RECOMMENDATIONS To enhance employee engagement, organizations should prioritize a tailored approach to incentives. While providing a competitive salary and bonuses with a diverse fringe benefit package is critical, other factors such as a secure and stable workplace, work-life balance, positive relationships with colleagues, and opportunities for home office should also be offered. These rewards should be customized based on the backgrounds and personalities of the employees to maximize engagement and satisfaction.